PERBAIKAN FASILITAS KERJA MEMBATIK DENGAN PENDEKATAN ERGONOMI UNTUK MENGURANGI MUSCULOSKELETAL DISORDERS - Sanjaya, Krishna Tri; Wahyudi, Slamet; Soenoko, Rudy (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2013)
Small and middle enterprises have been the important part of the economic of a nation or a local. Karang Write-Batik is one industrial center which is located at Karang Village, Semanding Subdistrict, Tuban District. Early observation shows that various processes within the production of Write-Batik are conducted without considering ergonomic aspects, such as work method and work facility. It may result in complaint and even muscle injury which is called Musculoskeletal Disorders (MSD’s) Many pronlem of pain perceived by workers are caused by less ergonomic work position or work posture. It may also be evident because the less correspondence between work equipment and workers’ anthropometry size. To measure workers’ musculoskeletal injured, the author uses Standard Nordic Questionnaire (SNQ) and to assess work posture, Quick Exposure Check (QEC) is used. The reduction of workers’ musculoskeletal injuredt can be realized by improving work facility based on workers’ anthropometry size. Result of early measurement of exposure level of several parts of body indicates that the exposure level of the back is 26, while that of the arm is 30, that of the hand wrist is 26, and that of the neck is 16. After the improvement of work facility, workers’ complaint is reduced and so is exposure level. The exposure level with the improved work facility is shown as follows: the exposure level of the back is 22, while that of the arm is 22, that of the hand wrist is 22 and that of the neck is 14.